Verification of the influence of liver microstructure on the evaluation of shear wave velocity. (23rd April 2021) - Ito, Daiki; Oguri, Takuma; Kamiyama, Naohisa; Hirata, Shinnosuke; Yoshida, Kenji; Yamaguchi, Tadashi
Abstract: Previous studies have shown that evaluation results of shear wave elastography were unstable due to factors such as liver structure and complexity of physical properties. The present study attempts to verify the influence of liver microstructure (fat droplets and fibrous tissue) on the shear wave and shear wave velocity (SWV) evaluation using a shear wave propagation simulation by the elastic finite-difference time-domain method. It was found that disruption of the shear wave causes variations in the SWV of the liver around fat droplets, and the SWV of the fibrous tissue depends on the shear wave propagation direction and the tissue shape. In a nonalcoholic steatohepatitis liver, which contains fat and fiber, the influences of these two tissues are synergistically reflected in the SWV evaluation.